The Role of Auditory and Visual Working Memory Capacity in Metasyntactic Abilities - Abumousa, Raneem; Alhamouri, Firas (Dirasat: Educational Sciences, 2021)
The present study aims to explore the role of auditory and visual working memory capacity in metasyntactic abilities, among a sample of 134 undergraduate students from the scientific and humanity colleges in Yarmouk University. Participants carried out four tasks: nonword repetition task to measure the auditory working memory capacity, recall the different shape test to measure the visual working memory capacity and error replication task; (copying semantic error) to measure the metasyntactic abilities in visual and auditory tests. The results indicated that the level of the students in both auditory metasyntactic abilities, and working memory capacity were higher than both visual metasyntactic abilities, and working memory capacity, respectively. There were statistically significant relationships between the metasyntactic abilities with both auditory and visual metasyntactic abilities. Finally, the results indicated that auditory working memory capacity, college type and gender, explained (16.4%) in the variance of visual metasyntactic ability.